The Perceived Importance of Communication Skills Course among University Students: The Case of Two Universities in Tanzania - Sotco Claudius Komba (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2016)
This article is based on a study which was conducted to examine the perceived importance of communication skills course among Tanzanian university students. A total of 134 undergraduate students, randomly selected from two Tanzanian universities, were involved in this study.  The study adopted a case study design in order have an in-depth understanding of the phenomenon under investigation. Both a questionnaire and interview schedule were used to collect data from the respondents. The collected data were analysed using thematic content analysis. It was revealed that the communication skills course was perceived by the majority of the respondents as an important course for the acquisition of communication skills needed in academic settings. It is recommended that universities should improve the delivery of the course by ensuring that both human and material resources are adequately available for the realization of the anticipated course outcomes.